Elementos de protección personal (EPP) para el uso seguro del motocultivador - Centis, Damiano; Pachinsky, Orlando Jesus; Kostecki, Jorge; Gomez, Agustin Dionisio (Estación Experimental Agropecuaria Sáenz Peña, INTA, 2024)
Folleto informativo